2023
DOI: 10.1186/s12889-022-14355-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on incidence and relevant factors of allergies in 5725 urban pregnant women: a cohort study in China

Abstract: Background Allergic diseases are highly prevalent in the women of childbearing age. As we know, the immune system could change when pregnancy, which may affect the course of allergic diseases. Meanwhile, they also can affect the course and outcome of pregnancy. The data on incidence of allergies during pregnancy is lacking and conducting clinical trials in pregnant women was limited, therefore, we observed a prebirth cohort to supplement the relevant data and strengthen concerned research condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The prevalence of exacerbations during pregnancy also showed an increasing trend, from 0.17% in 2013 to 0.42% in 2020. A large-scale study conducted across 20 municipal and higher institutions in 14 Chinese provinces reported in 2023 that the prevalence of asthma during pregnancy was 0.3% [ 5 ]. According to data from a South Korean population, 0.43% of pregnant women had asthma between 2009 and 2011 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of exacerbations during pregnancy also showed an increasing trend, from 0.17% in 2013 to 0.42% in 2020. A large-scale study conducted across 20 municipal and higher institutions in 14 Chinese provinces reported in 2023 that the prevalence of asthma during pregnancy was 0.3% [ 5 ]. According to data from a South Korean population, 0.43% of pregnant women had asthma between 2009 and 2011 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is the most prevalent respiratory disorder that complicates pregnancy, and the prevalence of asthma in pregnancy was 0.3% in China [ 4 , 5 ]. Asthma is linked to complications during pregnancy, poor perinatal outcomes, and allergic diseases in the offspring [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the incidence of allergic diseases shows an increasing trend, there has been a growing concern about allergies. Dietary ingredients, pollen and mites can all be allergens that trigger allergic diseases 37 . Wheat, one of the top eight food allergens, is present in a variety of staple foods, snacks and beverages, and is also a common allergy trigge [1][2][3] .…”
Section: Discussionmentioning
confidence: 99%
“…Allergic diseases occur in approximately 21% of urban pregnant women. 1 Atopic dermatitis (AD) is the most common one, making up to 50% of pregnancy dermatoses. 2 However, patch-testing is not recommended for pregnant and breast-feeding women, as their immunological changes preclude correct response.…”
Section: Introductionmentioning
confidence: 99%